Dakwah Lingkungan Perspektif Al-Qurâan - Muhyiddin, Asep (Jurnal Ilmu Dakwah, 2010)
Daâwah have tight catch with various etnics, one of them called the environment problem. This entity can be parameter ifÂ  daâwah activity can give contribution to solute environmental problems. These problems can examine the exsistence of daâwah truth. Al-Qurâan as the holybook of daâwah have viewÂ  that the nature is not enemy that has to subjected and submitted, but integrated with human religious world. Al- Qurâ an give moral command that related by this assignment of daâwah practicioner. One-in order to man be active practicioner in managing the environment. Two-in order to man not doing damage to environment. Three- in order to man be friendly to environment.